2014
DOI: 10.1590/0034-76121651
|View full text |Cite
|
Sign up to set email alerts
|

A percepção dos gestores operacionais sobre os impactos gerados nos processos de trabalho após a implementação das melhores práticas de governança de TI no TRE/SC

Abstract: Rev. Adm. Pública -Rio de Janeiro 48(4): 961-982, jul./ago. 2014 A percepção dos gestores operacionais sobre os impactos gerados nos processos de trabalho após a implementação das melhores práticas de governança de TI no TRE/SC Rosangela Klumb Tribunal Regional Eleitoral de Santa Catarina Beatriz Marcondes de Azevedo Universidade Federal de Santa CatarinaEste estudo objetivou compreender a percepção dos gestores operacionais da Secretaria de Tecnologia da Informação (STI) do TRE/SC acerca dos impactos gerad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Klumb and Azevedo [30] investigated the managers' view and the impacts generated in the internal work processes of the Regional Electoral Court of the State of Santa Catarina (Tribunal Regional Eleitoral de Santa Catarina (TRE/SC)), after the implementation of ICT Governance practices. The results showed that there was an increase in efficiency, agility, and quality of the services made available to users by the Information Technology Services Center, reflecting positively on the quality of the services provided.…”
Section: Related Workmentioning
confidence: 99%
“…Klumb and Azevedo [30] investigated the managers' view and the impacts generated in the internal work processes of the Regional Electoral Court of the State of Santa Catarina (Tribunal Regional Eleitoral de Santa Catarina (TRE/SC)), after the implementation of ICT Governance practices. The results showed that there was an increase in efficiency, agility, and quality of the services made available to users by the Information Technology Services Center, reflecting positively on the quality of the services provided.…”
Section: Related Workmentioning
confidence: 99%
“…The COBIT model was created at the end of the 1990s by the IT Governance Institute (Klumb & Azevedo, 2014;Luciano & Testa, 2011). Its goal is related to the control of IT practices rather than their execution, with the most important aspects providing strategic alignment of IT to business in order to maximize returns, ensuring that IT resources are used sparingly and that risks associated with IT are mitigated (Klumb & Azevedo, 2014;Luciano & Testa, 2011).…”
Section: Maturity Model In It and The Cobit Modelmentioning
confidence: 99%
“…Its goal is related to the control of IT practices rather than their execution, with the most important aspects providing strategic alignment of IT to business in order to maximize returns, ensuring that IT resources are used sparingly and that risks associated with IT are mitigated (Klumb & Azevedo, 2014;Luciano & Testa, 2011). This practice is done to improve the quality of products and services, the suitability of resource use and investments, and compliance with organizational governance requirements (ITGI, 2007).…”
Section: Maturity Model In It and The Cobit Modelmentioning
confidence: 99%
“…Há diversas pesquisas empíricas que tratam sobre a GTI. Há estudos realizados sobre benefícios da TI e a relação com o desempenho empresarial (Albertin & Albertin, 2008); utilização dos critérios de efetividade da GTI (Sortica & Graeml, 2009); adoção das práticas de modelos de GTI (Barbosa, Araújo, & Torres, 2011;Tarouco & Graeml, 2011); gerenciamento e controle de operação (Luciano & Testa, 2011); mecanismos para melhorar o desempenho financeiro (Lunardi, Becker, & Maçada, 2012); revisão da literatura sobre recursos de TI sob as diferentes correntes de pesquisa e frameworks de governança (Hiekkanen et al, 2013); sistema de apoio à tomada de decisão inteligente (Arshad, Ahlan, & Ajayi, 2014); impactos gerados nos processos de trabalho (Klumb & Azevedo, 2014); ferramenta na gestão de negócios (Duarte, Kipper, Paz, & Mariani, 2015); resolução de conflitos e eficiência na implementação e consecução de objetivos de negócios em programas de TI (Parolia, Jiang, Chen, & Klein, 2015); análise da dimensão alinhamento estratégico nas Universidades Federais Brasileiras (Putz et al, 2017); e benefícios da TI para as estratégias empresariais (Moura et al, 2018).…”
Section: Introductionunclassified